Robotics in Genitourinary Surgery (Springer International Publishing, 2018)
This updated volume provides a comprehensive guide to the recent developments of digital and intelligent technologies related to genitourinary surgery. New topics include the adaptation of simulators, training programs, standardized credentialing, evidence-based practice, as well as the economics of robotic surgery. The impact on public and global health is also covered. Robotics in Genitourinary Surgery aims to help surgeons and patients adopt the techniques and procedures discussed, and in turn educate and expand research activities within the field.